Aberrant Articulation of Cervical Vertebral Transverse Process: An Uncommon Normal Variant and Review of the Literature - Song, Yoonah; Ryu, Jeong Ah; Cha, Seung Woo; Lee, Seunghun; Joo, Kyung Bin (Journal of the Korean Society of Radiology, 2013)
Aberrant articulation between two anterior tubercles is a rare congenital anomaly that should be considered for patients showing a bony projection anterior to the vertebral body on a lateral radiograph of the cervical spine. We present a case of an elongation of the anterior tubercles of the transverse processes of both the fifth and sixth cervical vertebrae. This finding is probably a form of supernumerary cervical rib developing at a level above the lowest cervical spine. KCI Citation Count: 0